1997
DOI: 10.1111/1523-1747.ep12319025
|View full text |Cite
|
Sign up to set email alerts
|

Human Desmocollin 1 (Dsc1) Is an Autoantigen for the Subcorneal Pustular Dermatosis Type of IgA Pemphigus

Abstract: IgA pemphigus showing IgA anti-keratinocyte cell surface autoantibodies is divided into subcorneal pustular dermatosis (SPD) and intraepidermal neutrophilic IgA dermatosis (IEN) types. We previously showed by immunoblotting that IgA from some IgA pemphigus patients reacted with bovine desmocollins (Dsc), but not human Dsc. To determine the antigen for IgA pemphigus, we focused on conformation-dependent epitopes of Dsc, because sera of patients with classical pemphigus recognize conformation-sensitive epitopes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
150
0
9

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 199 publications
(163 citation statements)
references
References 29 publications
4
150
0
9
Order By: Relevance
“…Previous studies have not identified significant Dsc3 autoreactivity in the sera of PV patients. However, many of these studies used ELISA, which has been shown to be suboptimal for detecting autoreactive antibodies to desmocollin 1 in cases of IgA pemphigus, 32 potentially due to destruction or masking of epitopes. We have similarly found that autoreactive Dsc3 epitopes are not significantly detected by ELISA testing of pemphigus sera, in part due to the sensitivity of these epitopes to freezing and thawing (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not identified significant Dsc3 autoreactivity in the sera of PV patients. However, many of these studies used ELISA, which has been shown to be suboptimal for detecting autoreactive antibodies to desmocollin 1 in cases of IgA pemphigus, 32 potentially due to destruction or masking of epitopes. We have similarly found that autoreactive Dsc3 epitopes are not significantly detected by ELISA testing of pemphigus sera, in part due to the sensitivity of these epitopes to freezing and thawing (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…10 European Journal of Human Genetics Desmosomal cadherin mutations DM Hunt et al 201 structure and function in the epidermis. Similarly although some cases of pemphigus have now been attributed to desmocollin autoantigens, 45 nevertheless most pemphigus cases are due to autoimmunity involving Dsg1 and Dsg3. The desmogleins differ from the desmocollins in containing a region at their C-terminus made up of a number of unique repeats which is predicted to form an anti-parallel b-sheet and which can be visualised as a knob-like structure.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20] Subepidermal bullous dermatosis Bullous pemphigoid IIF: It shows circulating antibodies of the anticollagen XVII (BP180) IgG class in 70% of the patients. It appears that there is no correlation between antibody titers and the extension or activity of the disease.…”
Section: -1842mentioning
confidence: 99%